Sleeve lobectomy for an arteriovenous malformation in the bronchus intermedius in a child - Aditya Sengupta; Othman Aljohani; Howaida El-Said; Aparna Rao; Matthew Brigger; Raghav Murthy (Elsevier, 2019)
Arteriovenous malformations within the tracheobronchial tree in pediatric patients uncommonly present as hemoptysis, and can usually be treated with percutaneous transcatheter embolization. When this fails, parenchymal-sparing operations are needed. While these have been popularized for the management of bronchial neoplasms in children and adults, such bronchoplastic techniques are not commonly performed in children with tracheobronchial vascular malformations and acute hemoptysis. Here, we present a patient with recurrent hemoptysis who was found to have an arteriovenous malformation in the bronchus intermedius, and had failed numerous attempts at coil embolization. Via a right thoracotomy approach, we successfully performed a right middle lobectomy and sleeve resection of the bronchus intermedius. The post-operative recovery was uneventful, and there were no further episodes of hemoptysis. Thus, by applying the principles of bronchoplastic resection, such parenchymal-preserving surgery can be successfully used to manage symptomatic bronchial arteriovenous malformations with hemoptysis. Keywords: Pulmonary arteriovenous malformation, Tracheobronchial, Sleeve lobectomy, Bronchoplastic resection, Bronchus intermedius, Failed embolization